2004
DOI: 10.1213/01.ane.0000106860.27791.44
|View full text |Cite
|
Sign up to set email alerts
|

Xenon and Isoflurane Differentially Modulate Lipopolysaccharide-Induced Activation of the Nuclear Transcription Factor KB and Production of Tumor Necrosis Factor-?? and Interleukin-6 in Monocytes

Abstract: This study has shown that monocytes respond to lipopolysaccharide (LPS) in the presence of xenon with an increased activation of nuclear transcription factor (NF)-kappaB, whereas isoflurane inhibits LPS-induced activation of NF-kappaB. These findings suggest a possible molecular mechanism for the different effects of both anesthetics on monocyte tumor necrosis factor-alpha and interleukin-6 production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 17 publications
6
29
3
3
Order By: Relevance
“…It has been suggested that Xe interacts with the immune system by preserving neutrophil and monocyte antibacterial capacity and modulation of inflammatory cytokines such as tumor necrosis factor-a and interleukin-6 in monocytes. 38,39 In the present study, Xe had no effect on the commonly monitored inflammatory marker CRP. We compared degree and timing of the individual CRP responses withdatafrommatchedchildren undergoing cooling only.…”
Section: Figurecontrasting
confidence: 60%
“…It has been suggested that Xe interacts with the immune system by preserving neutrophil and monocyte antibacterial capacity and modulation of inflammatory cytokines such as tumor necrosis factor-a and interleukin-6 in monocytes. 38,39 In the present study, Xe had no effect on the commonly monitored inflammatory marker CRP. We compared degree and timing of the individual CRP responses withdatafrommatchedchildren undergoing cooling only.…”
Section: Figurecontrasting
confidence: 60%
“…There is increasing evidence that these properties are mediated by inhibition of proinflammatory intracellular signal transduction pathways (17). Accordingly, it was demonstrated in animal models of LPS administration that the release of proinflammatory cytokines is markedly reduced by exposure to volatile anesthetics (5,18).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro investigations suggest that xenon has pro-inflammatory effects, increasing TNF-α and IL-6 [66], and IL-1β [67] in LPSmediated cultures. A recent study on adults did not show any differences in leucocyte function in peripheral blood with xenon compared to sevoflurane [63].…”
Section: Inhalational Anestheticsmentioning
confidence: 99%